Skin and integumentary system (Henry Stewart Talks, 2026)
Skin structure and function, Major skin layers: epidermis, dermis, hypodermis, Skin appendages: hair, nails, glands, Skin cell types and functions, Skin structure variations and wound healing, Common skin disorders: eczema, acne, melanoma